USING ROUNDTABLE TECHNIQUE TO IMPROVE STUDENTS’ WRITING SKILL OF NARRATIVE TEXT - Evi Rosmiyati; Hj. Noviati Hj. Noviati (Esteem Journal of English Education Study Programme, 2022)
The objective of this study was to find out whether or not there is significant difference on teaching writing narrative paragraph through Roundtable Technique to the tenth grade students of Gajah Mada Vocational High School of Palembang. This study applied quasi-experimental method with non-equivalent control group design. The population of this study was all tenth grade students of Gajah Mada Vocational High School of Palembang, in the academic year of 2021/2022 with the total number of 216 students. The samples were 72 students, 36 students were in experimental group from X.1 class and 36 students were in control group from X.2 class taken by using purposive sampling. In collecting the data, a written test of the recount text was used, and the data were analyzed by using Application of IBM SPSS Statistics 23. The result of this study showed that the experimental group students’ average score in pre-test, it was 64.32, and in post-test, it was 71.66 while the control group students’ average score in pre-test was 64.50 and in post-test, it was 65.70. The value of t-obtained was (3.843) which were higher than the value of t-table (2.004) at the significance 0.05 in two tailed-test with 54 (df). It was assumed that the null hypothesis (Ho) was rejected, and the alternative hypothesis (Ha) was accepted. It means that there was significant difference on teaching writing of Gajah Mada Vocational High School of Palembang and those who were not.